방사선관리구역내의 종사자 및 임상실습 학생의 개인피폭선량 비교 분석 - 이주아(Joo-Ah Lee) (한국콘텐츠학회 논문지, 17(11), 2017)
The purpose of this study was to compare radiation dose among workers in the radiation zone and to compare the doses of students in clinical practice in the same area to provide basic data on optimization of radiation protection. The subjects were 121 radiation related workers, 36 radiation workers, and 121 students who completed 8 weeks of clinical practice from Jan. 2016 to Dec. The depth and surface dose between the radiation related workers and the radiation workers were the highest with $.7440{±}1.676mSv$ and $.7753{±}1.730mSv$, respectively, and statistically significant (p<.01). Among the three groups, the depth dose was the highest at $.143{±}.136mSv$ for clinical practice students and the highest at surface dose of $.1513{±}.139mSv$. The lowest in both cases, The mean difference between the two groups was statistically significant (p<.01). In conclusion, it is necessary to manage thoroughly according to the ALARA(As Low As Reasonably Achievable) principle. Especially, it is necessary to systematically manage the dose of radiation for clinical students who are in the blind spot of radiation safety management. 방사선구역내의 종사자 간 선량 비교 및 동일한 구역 내에서 임상실습에 임하는 학생들의 선량을 추가하여 비교함으로써 방사선방어의 최적화 구현에 대한 기초자료를 제공하고자 하였다. 연구 대상은 2016년 1월부터 동년 12월까지 C대학병원 방사선 관리구역에 재직 중인 방사선관계종사자 121명과 방사선작업종사자 36명, 그리고 8주간의 임상실습을 이수한 121명의 학생을 비교 대상으로 하였다. 방사선관계종사자와 작업종사자 간의 심부 및 표층 선량은 관계종사자가 각각 $.7440{±}1.676mSv$와 $.7753{±}1.730mSv$로 가장 높게 나타났으며, 통계적으로 매우 유의하였다(p<.01). 세 그룹 간에는 심부 선량의 경우 임상실습학생이 $.143{±}.136mSv$로 가장 높게 나타났고, 표층 선량에서도 $.1513{±}.139mSv$로 가장 높게 나타났으며, 작업종사자가 두 경우 모두 가장 낮았다. 그룹 간의 평균의 차이는 통계적으로 매우 유의하였다(p<.01). 결론적으로 ALARA(As Low As Reasonably Achievable)원칙에 의거 철저한 관리가 필요하며, 특히 방사선안전관리의 사각지대에 놓여 있는 임상실습 학생에 대한 체계적인 피폭선량 관리가 필요할 것으로 사료된다.